Vaginal ectopic ureter diagnosed by magnetic resonance imaging in a child with complete transverse vaginal septum and hydrocolpos - Lucena, Iara Regina; Duarte, Juliana Avila; Takamatu, Eliziane E.; Garcia, Clotilde D.; Costa, Eduardo C.; Furtado, Alvaro PA; Fraga, Jose Carlos (Clinical and Biomedical Research, 2014)
Ectopic ureter draining into the vagina is a rare cause of urinary incontinence. Some cases have been reported in association with malformations of the genitourinary tract, but very few published cases are associated with vaginal septum. Our article describes the case of a girl who presented with hydrocolpos shortly after birth and was found to have a complete transverse vaginal septum. Despite successful correction of this genital anomaly, the patient developed persistent dribbling of clear fluid from the genital area. Extensive testing revealed unilateral kidney dysplasia and probable genital ectopia of the corresponding ureter. Magnetic resonance imaging (MRI) showed insertion of the ureter into the upper third of the vagina. The patient underwent nephroureterectomy of the dysplastic kidney with subsequent improvement in urinary incontinence. Ureteral ectopia is difficult to diagnose with conventional imaging methods (plain radiography, ultrasound, and CT). MRI has proved to be an excellent method for assessment of genitourinary tract conditions, particularly when other diagnostic modalities have failed or are limited, due to the high resolution of MRI scans and the possibility of native image acquisition on all three orthogonal planes. MRI is the best diagnostic modality for visualization of the course and insertion of ectopic ureters, and enables precise surgical correction.